KONSEP KOMPETENSI GURU DALAM PERATURAN PEMERINTAH NOMOR 14 TAHUN 2005 TENTANG KOMPETENSI PEDAGOGIK, KEPRIBADIAN, PROFESIONAL, DAN SOSIAL PADA GURU - Gilang Luthfie Dalimunthe; Ahmad Yudha Pratama; Sutan Rizki Rambe (Cemara Education and Science, 2024)
The Indonesian government has issued various regulations regulating teacher competency with the aim of improving the quality of education. This regulation covers four aspects of teacher competence: pedagogical, personality, professional and social. Pedagogical competence is the teacher's ability to plan, implement and evaluate learning. Personality competency is related to the moral and ethical qualities that a teacher must have. Professional competence relates to a teacher's ability to guide learning and personal development. Social skills relate to the teacher's ability to build relationships with students, parents and the community. This regulation has several important implications for teachers, educational institutions and the government. For teachers, these rules serve as guidelines for developing personal skills. For educational institutions, this regulation is the basis for developing teacher training programs. For the government, this regulation is a tool to monitor and improve the quality of education.